Sociodemographical characteristics associated with adherence to treatment in adults with type 2 Diabetes - Cordero-Sánchez, Clemente; Alba-Alba, Corina; Muñoz-Covarrubias, Madai; Guzmán-Ortiz, Elizabeth; Ramirez-Giron, Natalia (Horizonte Sanitario, 2022)
Objective: To establish the association of sociodemographic characteristics and treatment adherence in Mexican adults with Type 2 Diabetes. Materials and Methods: A descriptive, cross-sectional study was made in Mexican adults over 18 years with Type 2 Diabetes who attended a diabetes clinic of a public hospital. The sample were 100 adults. Conscious adults, diagnosed with DT2, with a minimum evolution of three years with the diagnostic were included. The Morisky, Green and Levine´s test was used to identify the adherence to the treatment. Results: The female sex predominated (62%), the adults between 50-59 years were the most representative group (59%); el 46% had primary school and 69% were married. The 23% of the sample has 3 years with the diagnostic, only 38% of the respondents do exercise 10-15 minutes a day and 28% did not do exercise; the majority report having a pharmacological treatment based on oral hypoglycemic agents (82%). The age was associate with the adherence to the treatment (p<.005). Conclusions: Age was the only sociodemographic characteristic that was significantly associated with adherence to treatment in Mexican adults with Type 2 Diabetes. Health personnel, mainly those at the first level of care, should focus on promoting adherence to treatment in patients suffering from DT2, taking into account their sociodemographic characteristics, especially age. Key words: Treatment adherence and compliance; Type 2 diabetes; Community health nursing.